PHILOSOPHY OF WAR AND PEACE: IN SEARCH OF NEW EUROPEAN SECURITY STRATEGY - O. O. Bazaluk; D. B. Svyrydenko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Introduction. The contemporary European social and cultural landscape feels the pressure of security challenges. It is true, that Europe has a strategy of overcoming the possible challenges, but it has sense to review ones strategy abilities to be effective at the face of new manifestations of aggression. Methodology. The authors use heuristic philosophical methodology which can make mentioned strategy more holistic having clear vision of the essence of war and peace phenomena. The research is going to perform precious conceptualization of the strategy contours initiated at the previous publications of O. Bazaluk. Originality. Authors defined the series “fatal” mistakes of the European Security Strategy and formulated the list of objectives of the revised security strategy. Conclusions. Five key objectives of perspective European Security Strategy were formulated. The first objective should include the complex measures for the identification, registration and organization of the system of preventive work with mentalities, in which the pathologies in the structure and function of the neural ensembles of subconsciousness and consciousness are clearly expressed that refract the active principle (as natural force) in aggressive manifestations. The second one should include the complex measures ensuring control over the direction of the physicochemical, predisposing, provoking and supporting factors of the external environment that have a direct impact on the manifestations of a mental space in ontogeny. The third objective should include the complex measures of prediction and solution of international (interstate) conflicts. The fourth objective of the security strategy should be aimed at eliminating the cause of war. The fifth objective should provide the complex measures involving the peaceful extension of comfortable conditions for the full realization of its internal creative potentials by a mental space.